Examining toxic leadership, pay satisfaction and LMX among nurses: evidence from Ghana - Dartey-Baah, K.; Quartey, S.H.; Asante, K.G. (Industrial and Commercial Training, 2023)
Purpose – The purpose of this paper is to establish a relationship between pay satisfaction and leader–member relationship and examine pay satisfaction as a moderator of the relationship between toxic leadership and LMX among public sector nurses in Ghana. Design/methodology/approach – Using a cross-sectional survey approach, the authors used questionnaires to collect data from 225 nurses working in public hospitals in Ghana. The hypotheses were tested using covariance-based structural equation modelling. Findings – The results of this study revealed that pay satisfaction levels of nurses had an influence on leader–member exchange (LMX). The results further showed that pay satisfaction as a moderator of the relationship between toxic leadership and LMX was not statistically significant. Research limitations/implications – Cross-sectional surveys are often criticised for causality issue. The causality issue here is that the link between toxic leadership, pay satisfaction and LMX was explored at a given point in time and ignores changes through time. Practical implications – Hospitals must encourage their leaders to demonstrate more supportive and positive behaviours to foster positive leader–member relationships. Maladjusted, malcontent and malevolent leadership behaviours are dangerous for nurses and hospitals and can be addressed through leadership training and development. Social implications – Toxic leadership has considerable organisational costs of low productivity and negative work relationship at the workplace. The indirect effects of toxic leadership at the workplace on employees’ families and friends are often silent in organisations. Originality/value – Nurses have been ignored in toxic leadership research in emerging economies. LMX is extended to examine toxic leadership and pay satisfaction in public hospitals in an emerging economy
Research Article
Keywords: Toxic leadership; Pay satisfaction; Public hospitals